2017
DOI: 10.5114/biolsport.2017.65336
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined supplementation of carbohydrates and creatine on anaerobic performance

Abstract: The purpose of the study was to examine the effect of creatine (Cr) supplementation on anaerobic performance when ingesting creatine and carbohydrates (CHO) together. Twenty male physical education students comprised the two experimental (CR and CRCHO) and one control (CON) groups of the study. All groups performed three 30 s anaerobic Wingate tests (AWTs) interspersed with 6 minutes of recovery. The CR group (n = 7) ingested 5 g of Cr 5 times per day for 4 days. Subjects in the CRCHO group (n = 6) ingested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
4
0
4
Order By: Relevance
“…A suplementação de creatina sozinha não teve qualquer efeito sobre a concentração de insulina, porém, a ingestão de creatina associada ao carboidrato aumentou os níveis desse hormônio de maneira significativa. As descobertas encontradas demonstram que a ingestão de CHO aumenta a creatina muscular de forma substancial durante a ingestão de creatina (Theodorou et al, 2017). Tomcik et al (2018) investigaram os efeitos metabólicos e de desempenho de uma combinaçãode creatina (CR) e carboidratos (CHO) em ciclistas de contrarrelógio (TT).…”
Section: Capacidade De Exercícios E Esforços Prolongados De Alta Inte...unclassified
“…A suplementação de creatina sozinha não teve qualquer efeito sobre a concentração de insulina, porém, a ingestão de creatina associada ao carboidrato aumentou os níveis desse hormônio de maneira significativa. As descobertas encontradas demonstram que a ingestão de CHO aumenta a creatina muscular de forma substancial durante a ingestão de creatina (Theodorou et al, 2017). Tomcik et al (2018) investigaram os efeitos metabólicos e de desempenho de uma combinaçãode creatina (CR) e carboidratos (CHO) em ciclistas de contrarrelógio (TT).…”
Section: Capacidade De Exercícios E Esforços Prolongados De Alta Inte...unclassified
“…One study of endurance-trained cyclists and triathletes demonstrated that combined creatine and carbohydrate loading produced increases in power performance for intermittent cycling sprints between longer time trials, and observed increased muscle concentrations of creatine phosphate and glycogen (29). A couple of other studies, however, found no effects of creatine and carbohydrate coingestion on anaerobic performance with Wingate cycling and maximal running tests (30,31).…”
Section: Mixed Supplementationmentioning
confidence: 99%
“…Um estudo recente realizado por Theodorou et al (2017) no Reino Unido, buscou investigar se a ingestão de creatina juntamente com carboidratos afetava a absorção e a retenção de creatina no corpo. Para a realização do estudo, foram recrutados 24 voluntários do sexo masculino ativos, que foram divididos em dois grupos.…”
Section: Creatina E Chounclassified
“…A suplementação de creatina sozinha não teve qualquer efeito sobre a concentração de insulina, porém, a ingestão de creatina associada ao carboidrato aumentou os níveis desse hormônio de maneira significativa. As descobertas encontradas demonstram que a ingestão de carboidratos aumenta a creatina muscular de forma substancial durante a ingestão de creatina (Theodorou et al 2017).…”
Section: Creatina E Chounclassified